SUARA YANG TERDIAM: NARASI PEREMPUAN DALAM KAJIAN KITAB KUNING TRADISIONAL - Cut Dewi Rahma (Yayasan An-Nur Meunara Baro, 2025)
This article explores the silenced voices of women within the corpus of traditional Islamic texts known as kitab kuning, a field long dominated by male interpretations that often marginalize female perspectives. Employing genealogical tracing and critical ethnography, this study investigates classical manuscripts and practices in female Islamic boarding schools (pesantren) to uncover traces of women’s intellectual contributions embedded in marginalia, oral traditions, and gender-specific pedagogies. Findings reveal that women are not entirely absent from Islamic knowledge production, but rather systematically marginalized through the structural mechanisms of canon formation. Texts often assumed to be gender-neutral in fact carry ideological underpinnings that sustain patriarchal dominance. Yet, silence within the texts can also be interpreted as a form of symbolic resistance, signaling women’s presence in unexpected ways. A gender-sensitive rereading of kitab kuning opens up possibilities for reconstructing more just and inclusive narratives. This study recommends the deconstruction of traditional religious canons and the integration of feminist hermeneutics into Islamic education, as a means to create interpretative spaces that respond to women's lived experiences. Thus, the legacy of kitab kuning is not merely textual but demands epistemological critique in pursuit of a more equitable Islamic thought.